EFFECT OF INTERACTIVE PREGNANCY EDUCATION (IPE) ON STRESS LEVELS AMONG PRIMIGRAVID TRIMESTER III PREGNANT WOMEN - Elli Hidayati; Syahrul Rauf; Mochammad Hatta; Sonny T. Lisal; Fatimah; Hamidah (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
The Infant Mortality Rate (IMR) is an indicator in determining the health level of a country. Infant mortality is caused by various health problems, especially since the gestation period, even starting before the gestation period. Stress during pregnancy affects the motor, cognitive and emotional development of the baby. This study aims to determine the effect of Interactive Pregnancy Education (IPE) on levels in third trimester primigravida pregnant women. This research is a quasi-experimental study using a nonequivalent control group design. This research was conducted in the Kemayoran and Cempaka Putih Community Health Centers in DKI Jakarta from December 2021 to completion. The samples were 30 third trimester primigravida pregnant women for the intervention and control groups. Data were analyzed using the Mann Whitney and Wilcoxon tests with SPSS 22 software. The results showed that there was a significant difference between the median stress scores in the control group before and after the median decreased after the intervention and the difference in the median stress scores before and after the intervention in the intervention group was greater than the control group, which decreased to 6.50. This shows that IPE is effective in reducing stress in pregnant women who have previously had stress with high stress scores.